Analysis of service quality on customer satisfaction using the service quality method and analytical hierarchy process - Niera Feblidiyanti (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2025)
This research aims to analyze service quality and customer satisfaction to find out the factors of consumer/customer complaints so that company performance can be improved and improved. This research uses the Servqual method, the company can then find out consumers' perceptions and expectations, while the company's AHP method can sort out which criteria are prioritized first to improve service quality so that the hospital becomes better. The results of the research were conducted with a sample of 100 respondents and 20 question items. In calculating the weighted servqual the priority for improving the quality of service in the Tangible dimension is the criterion